Empowerment of Kader Kesehatan Jiwa (KKJ) through RW Siaga Sehat Jiwa (RW SSJ) in Bandarharjo Semarang - Dwi Heppy Rochmawati (Universitas Islam Sultan Agung, 2019)
Health is an investment to improve the quality of human resources. Both physically and psychologically healthy. The mental nursing area includes giving care to healthy mental, client and mental disorders clients. Mental health services are no longer focused on healing clients of mental disorders, but also on efforts to promote mental health or prevention efforts. This effort can be carried out by health workers and community participation through community empowerment. Community empowerment of mental health can be achieved with a health service management especially community-based mental health services. This form of health care management approach is known as Community Mental Health Nursing (CMHN). The purpose of this community service is to realize the formation of RW Siaga Sehat Jiwa (RW SSJ) with the participation of the Mental Health Cadre (KKJ). RW SSJ is a forum for the KKJ to carry out activities and apply the abilities obtained through training. With the increasing ability of the KKJ in overcoming health problems, it is hoped that the community can play an active role in realizing health status in their environment. The method used is the nursing process approach. It is expected that the KKJ has the ability to carry out early detection, determine family status and care for family risks and disorders, refer cases to health centers and or hospitals.